Admittance of transverse waveguide slots in cylindrical structures. - Wettergren, J. (IEEE Transactions on antennas and propagation)
The self and mutual admittances of transverse slots in arbitrary conducting cylindrical structures are computed. The analysis is performed in the spectral domain, where all fields and currents have been Fourier transformed along the structure. There are, however, no transformations in the transverse directions. A system of integral equations for cylindrical structures are formulated and solved with the moment method. The induced currents on the structure can thus be determined and used to compute the spectral self and mutual admittance of the slots. The spectral admittance is inverse transformed and included in the overall slot antenna analysis. The analysis is rigorous with trigonometric basis function expansions at the inner and outer slot apertures. Computed results on scattering parameters in the waveguide show good agreement with measured data